2014
DOI: 10.1177/0954411914548700
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of low bone mass using a combinational approach of cortical and trabecular bone measures from dental panoramic radiographs

Abstract: The aim of this study is to extract cortical and trabecular features of the mandible and to develop a novel combinational model of mandibular cortical thickness, trabecular bone area and age in order to predict low bone mineral density or osteoporosis from a dental panoramic radiograph. The study involved 64 south Indian women (age = 52.5 ± 12.7 years) categorised into two groups (normal and low bone mineral density) based on total femur bone mineral density. The dental panoramic radiographs were obtained by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
(45 reference statements)
0
12
0
1
Order By: Relevance
“…Groups of participants diagnosed with osteoporosis were compared against patients considered as having normal BMD in 10 studies (Chai, Chau, Chung, & Chow, ; Kathirvelu & Anburajan, ; Khojastehpour, Mogharrabi, Dabbaghmanesh, & Nasrabadi, ; Lee & White, ; Mostafa, Arnout, & Fotouh, ; Oliveira et al, ; Roberts, Graham, & Devlin, ; Sindeaux et al, ; Tosoni, Lurie, Cowan, & Burleson, ; Yamashita‐Mikami et al, ). Radiographic modalities such as conventional film and digital panoramic, intraoral film radiographs, CT, and micro‐CT scans were explored and compared to the BMD score.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Groups of participants diagnosed with osteoporosis were compared against patients considered as having normal BMD in 10 studies (Chai, Chau, Chung, & Chow, ; Kathirvelu & Anburajan, ; Khojastehpour, Mogharrabi, Dabbaghmanesh, & Nasrabadi, ; Lee & White, ; Mostafa, Arnout, & Fotouh, ; Oliveira et al, ; Roberts, Graham, & Devlin, ; Sindeaux et al, ; Tosoni, Lurie, Cowan, & Burleson, ; Yamashita‐Mikami et al, ). Radiographic modalities such as conventional film and digital panoramic, intraoral film radiographs, CT, and micro‐CT scans were explored and compared to the BMD score.…”
Section: Resultsmentioning
confidence: 99%
“…For panoramic radiographs, Oliveira et al () found strong positive rank coefficient ( r ) correlation ( r = 0.90) between fractal dimension analysis of the mandibular body and osteoporosis in postmenopausal women ( p < 0.05). Kathirvelu and Anburajan () showed 84% inter‐reliability between radiologists while measuring radiographs. They segmented the average values of pixels as a threshold.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations